Identyfikacje ideologiczne społeczeństwa polskiego - Godlewski, Tomasz (Political Preferences, 2012)
This paper describes perception of the left and right-wing values by Polish commu- nity. They are analyzed in three dimensions: ideological and doctrinal, constitutional and eco- nomical as well as social. The outcome of the analysis was the creation of the map of actual per- ception of left and right wing by people with certain ideological auto-identification. The added value is a comparative analysis of the results obtained in 2012 with the data obtained from own studies conducted in 2007 that shows the dynamics of changes in the political consciousness of Polish society.